2007
DOI: 10.3168/jds.s0022-0302(07)71536-9
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Aflatoxin M1 to Different Protein Fractions in Ovine and Caprine Milk

Abstract: The affinity of aflatoxin M1 toward the main milk protein fractions in ewe and goat milk was investigated by using an ELISA. This study took into account the possible effects of common dairy processes such as ultrafiltration, acidic or rennet curding, and production of ricotta from acidic or rennet whey. Treatments that allowed the separation of casein from whey proteins under conditions that do not alter the physical or chemical status of the proteins (such as ultracentrifugation) were used as a reference. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 17 publications
5
28
0
1
Order By: Relevance
“…More specifically, cheese made with cows' milk showed itself to be more contaminated than cheese made with goat or sheep (or mixed goat/sheep, mixed goat/cow and sheep/cow) milk. This result agrees with the previous observation that milk from goats and sheep is less contaminated than cows' milk, both because of the different digestive apparatuses and mechanism of AFB1 assimilation of animals, and for the different feeding used in cow's breeding compared to ovine and caprine (Barbiroli et al, 2007;Hussain et al, 2010;Fallah et al, 2011). In fact, cattle fodders are more likely to be contaminated with AFB1 than those used to feed sheep and goats.…”
Section: Correlation Of Aflatoxin M1supporting
confidence: 82%
“…More specifically, cheese made with cows' milk showed itself to be more contaminated than cheese made with goat or sheep (or mixed goat/sheep, mixed goat/cow and sheep/cow) milk. This result agrees with the previous observation that milk from goats and sheep is less contaminated than cows' milk, both because of the different digestive apparatuses and mechanism of AFB1 assimilation of animals, and for the different feeding used in cow's breeding compared to ovine and caprine (Barbiroli et al, 2007;Hussain et al, 2010;Fallah et al, 2011). In fact, cattle fodders are more likely to be contaminated with AFB1 than those used to feed sheep and goats.…”
Section: Correlation Of Aflatoxin M1supporting
confidence: 82%
“…Several studies reported the binding affinity of AFM1 with the protein fraction in milk, and consequently the enhancement of its concentration in cheese as compared to milk (Barbiroli et al, 2007). Actually, a relevant portion of AFM1 remains in the whey, but this partitioning depends on the cheese-making procedure.…”
Section: Safety Of Food Of Animal Originmentioning
confidence: 99%
“…It is not surprising that paroxetine can also produce apoptosis in cancer cells, apparently due to the oquinone moiety, independently of its action on 5HT [Schuster et al, 2007]. A typical study of allylic ketones, especially adjacent allylic ketones, showed tight binding of an allylic toxin, aflatoxin M1, to milk proteins [Barbiroli et al, 2007]. g-Tocopherol is also metabolized to a quinone that can produce apoptosis and condense with GSH and protein thiols [Cornwell et al, 2003].…”
Section: Bioactivation Of ''Almost Allylic'' Drugsmentioning
confidence: 99%